Myelodysplastic Syndromes - Fuchs, Ota (IntechOpen, 2016)
This book is a comprehensive overview of myelodysplastic syndromes (MDS). MDS are a heterogeneous group of clonal hematopoietic stem cell disorders characterized by ineffective hematopoiesis, peripheral cytopenias, frequent karyotypic abnormalities, and risk of transformation to acute myeloid leukemia (AML). Median age of patients with MDS is about 70 years. Various immune abnormalities occur in MDS patients, and the relationship between autoimmune disorders and MDS is described. Accurate prognostication and risk stratification for individual patients with MDS are important for clinical treatment decisions. Patients with MDS are classified into two broad prognostic categories: lower risk and higher risk. The approval of lenalidomide, azacitidine, and decitabine in last 10 years helped to diminish the clinical impact of MDS and delayed its progression to AML.